The Effect Of Understanding Government Accounting Standards And The Utilization Of Accounting Information Systems On The Quality Of Financial Statements With Human Resource Competence As A Moderation Variable In The Asahan Regency Government - Register Launli Buaya; Oktarini Khamilah Siregar; Agus Tripriyono (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the influence of understanding Government Accounting Standards and the utilization of accounting information systems on the quality of financial statements in the Asahan Regency Government, with human resource competence as a moderating variable. The study is motivated by the need of local governments to produce financial reports that are reliable, relevant, and compliant with accrual-based accounting principles. However, challenges persist regarding the consistency of standard implementation, the effectiveness of information system utilization, and the adequacy of competencies among financial management personnel. This research employs a quantitative approach using a survey distributed to government officials involved in financial statement preparation. A questionnaire was used to collect data on respondents’ comprehension of SAP, the intensity and effectiveness of accounting information system usage, and their perceptions of financial report quality. The analysis was conducted using Moderated Regression Analysis (MRA) to examine the role of human resource competence as a strengthening or weakening factor in the relationships among variables. The results indicate that understanding SAP has a significant positive effect on the quality of financial statements. The use of accounting information systems also contributes significantly to improving financial information quality, particularly in aspects of timeliness, accuracy, and completeness. Furthermore, human resource competence was found to moderate the relationship between SAP understanding and information system utilization with financial report quality, where higher competence strengthens the effect of both variables. These findings emphasize the importance of capacity building through continuous training and optimization of information systems to support financial transparency and accountability in regional governments.